Late Roman warlords - MacGeorge, Penny; Oxford eBooks (Oxford : Oxford University Press, 2002)
This text reconstructs the careers of some of the men who shaped (and were shaped by) the last quarter century of the Western Roman Empire. An overview of earlier warlords, including Aetius is followed by studies of individual warlords and the regions they dominated.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Warlordism -- Rome; Rome -- Biography; Rome -- History -- Empire, 284-476.; Electronic books